Science-Islam Integration: A Critical Examination of Ziauddin Sardar's Epistemology and Its Relevance for Indonesian State Islamic Universities - Suhernawati, Suhernawati; Riadi, Haris; Aswati, Fajar; Azman, Wan; Susanti, Elya; Nasifah, Isri; Solehati, Citra (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: This study aims to explore Ziauddin Sardar’s epistemology in integrating modern science and Islamic values, focusing on Tauhid (Oneness of God), Khilafah (Stewardship), and Worship as foundational principles for the Islamization of science and their implications for Islamic higher education in Indonesia. Methodology: This research employs a qualitative descriptive-analytical method using a literature review approach. Primary sources include Sardar’s works on epistemology and the Islamization of science, while secondary sources comprise academic books, journal articles, and historical analyses. The study utilizes content analysis and comparative framework analysis to examine Sardar’s integration model within contemporary educational contexts. Main Findings: The study finds that the separation between science and Islam is influenced by historical, sociological, and political factors rather than Islamic teachings. Sardar’s epistemology provides a structured approach to integrating science with Islamic principles. His model offers a framework for curriculum development in state Islamic universities, promoting an interdisciplinary and ethical approach to knowledge. Novelty/Originality of this study: This study connects Sardar’s epistemology with the practical challenges of Islamic higher education in Indonesia, offering a structured framework for curriculum development. Unlike previous studies, it bridges Islamization theory with contemporary educational policy, providing a relevant and applicable model for integrating Islamic values into scientific disciplines.